About the choice of a plastic-like model for shape memory alloys - Lexcellent, C.; Laydi, R. M. (Vietnam Journal of Mechanics, 2011)
The aim of this paper is to examine the impact of the choice of plasticity theory-inspired model in the prediction of the shape of phase transformation domains. In this field a comparison is made between Huber-Von Mises based model and an another integrating the non-symmetry between tension and compression.  The yield surface of phase transformation initiation for a homogeneous body under proportional biaxial loading is discussed. A transport of these surfaces in the space of the "effective transformation strain of martensite tensor" is given.